Encyclopedia of Inorganic Chemistry 2005
DOI: 10.1002/0470862106.ia805
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis: Energy Conversion

Abstract: The process of water oxidation and carbon dioxide reduction in oxygenic photosynthesis involves a complex series of events that start with light energy capture and end with its storage in the form of the chemical energy in glucose. These reactions provide a solution to efficient solar energy conversion into high‐energy chemicals. The principles revealed by study of natural photosynthetic systems may be used to design artificial systems for solar fuel production. Understanding the light‐driven oxidation of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Therefore, although in natural systems the main functions of porphyrin-containing molecules, like enzymes and photosynthetic chlorophylls, proceed via π-radical cation intermediate products, ,, the cationic species of some Sn­(IV)­Ps might lead to the oxidative decomposition of water. In natural photosynthesis, the oxidation of excited P680 and P700 pigments gives rise to delocalized π-radical cations of chlorophylls in P680 .+ and P700 .+ (reduction potentials of 1.25 and 0.45 V, respectively) in the hydrophobic membrane which prevent side reactions. ,, In contrast, it was found that the reduced species metalloporphyrin π-radical anions are important intermediates in the photochemical reduction of protons to hydrogen on the surface of a catalyst. , Additionally, the unsuitability of oxidative quenching mechanisms for the excited state of Sn­(IV)­TPPC as a photosensitizer was discussed in ref . Another aspect is that even though the two-electron reactions and products are often favored for porphyrin compounds a metal center with a strong electronegativity (e.g., Sb­(V) or Sn­(IV)) pulls the electron density to the porphyrin core and stabilizes the product of the one-electron reduction π-radical anion by retarding porphyrin ring protonation, making π-radical anions of Sb­(V) or Sn­(IV) porphyrins stable (for minutes at neutral solutions and up to hours in alkaline solutions in the absence of an electron acceptor oxygen).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although in natural systems the main functions of porphyrin-containing molecules, like enzymes and photosynthetic chlorophylls, proceed via π-radical cation intermediate products, ,, the cationic species of some Sn­(IV)­Ps might lead to the oxidative decomposition of water. In natural photosynthesis, the oxidation of excited P680 and P700 pigments gives rise to delocalized π-radical cations of chlorophylls in P680 .+ and P700 .+ (reduction potentials of 1.25 and 0.45 V, respectively) in the hydrophobic membrane which prevent side reactions. ,, In contrast, it was found that the reduced species metalloporphyrin π-radical anions are important intermediates in the photochemical reduction of protons to hydrogen on the surface of a catalyst. , Additionally, the unsuitability of oxidative quenching mechanisms for the excited state of Sn­(IV)­TPPC as a photosensitizer was discussed in ref . Another aspect is that even though the two-electron reactions and products are often favored for porphyrin compounds a metal center with a strong electronegativity (e.g., Sb­(V) or Sn­(IV)) pulls the electron density to the porphyrin core and stabilizes the product of the one-electron reduction π-radical anion by retarding porphyrin ring protonation, making π-radical anions of Sb­(V) or Sn­(IV) porphyrins stable (for minutes at neutral solutions and up to hours in alkaline solutions in the absence of an electron acceptor oxygen).…”
Section: Introductionmentioning
confidence: 99%
“…Charge separation in photosystem I with additional electron located at the iron−sulfur cluster stores only 0.99 eV from the total energy (1.77 eV) absorbed by P 700 . 42 Therefore, in contrast to mitochondria the electrons "leaked" in photosystems are expected to occupy anion states lying 1− 1.5 eV above thermal energy, i.e., CPL is not able to interact with them. On the contrary, epithermal electron attachment to INA generates HCl and CO 2 species able to induce the defense response in plants.…”
Section: ■ Results and Discussionmentioning
confidence: 99%